2020
DOI: 10.1007/s00404-020-05889-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of pregnant women with COVID-19 and the risk of vertical transmission: a systematic review

Abstract: Purpose This systematic review summarizes the clinical features and maternal–infant outcomes of 230 pregnant women (154 patients gave birth) infected with COVID-19 and their 156 infants, including the possibility and evidence of vertical transmission. Methods An electronic search of PubMed, Embase, Medline, MedRxiv, CNKI, and the Chinese Medical Journal Full Text Database following PRISMA guidelines was performed through April 18, 2020. Search terms included COVID-19, SARS-CoV-2, pregnant women, infants, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
3
20

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(141 citation statements)
references
References 68 publications
5
93
3
20
Order By: Relevance
“…Several authors suggest that COVID-19 may trigger a severe systemic inflammatory response, with consequent MVM caused by the SARS-CoV-2 infection derived-hypoxia [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. We also recently reported [ 32 ] evidence of an increased immune activation profile in SARS-CoV-2 positive subjects, with higher levels of cytokines and chemokines in placental tissue, maternal and funicular plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors suggest that COVID-19 may trigger a severe systemic inflammatory response, with consequent MVM caused by the SARS-CoV-2 infection derived-hypoxia [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. We also recently reported [ 32 ] evidence of an increased immune activation profile in SARS-CoV-2 positive subjects, with higher levels of cytokines and chemokines in placental tissue, maternal and funicular plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The infection with SARS-CoV-2 has the potential to increase inflammatory and oxidative stress in the placenta, thus compromising both pregnancy evolution and fetal development [ 1 ]. Indeed, pregnancies complicated by SARS-CoV-2 infection have an increased risk of miscarriage, preterm birth, pre-eclampsia and stillbirth [ 2 , 3 , 4 ]. These pregnancy-related pathologies have long been known to be associated with an abnormal placental development.…”
Section: Introductionmentioning
confidence: 99%
“…A study states that delivery management should be determined according to medical indications and recommends vaginal delivery if there are no indications [ 11 ]. Furthermore, another study indicated that vertical SARS-CoV-2 transmission is all seen after cesarean delivery [ 12 ]. None of the babies delivered by cesarean were infected with SARS-COV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit still limited, there is evidence that SARS-Cov-2 can cause life-threatening situations also in pregnancy, even if fatal cases seem rare [5][6][7][8][9]. However, this evidence was mainly drawn from case series or selected referral centers, a study design that could overestimate the detrimental effects of SARS-Cov-2.…”
Section: Introductionmentioning
confidence: 99%
“…The fatality rate varies widely in the literature (1-22%) and depends on the clinical phase of the disease, gender, age and predisposing conditions such as diabetes, hypertensive disorders and obesity [3,4]. Albeit still limited, there is evidence that SARS-Cov-2 can cause life-threatening situations also in pregnancy, even if fatal cases seem rare [5][6][7][8][9]. However, this evidence was mainly drawn from case series or selected referral centers, a study design that could overestimate the detrimental effects of SARS-Cov-2.…”
Section: Introductionmentioning
confidence: 99%